Analisis Kontribusi Penerimaan Pajak Hiburan Dan Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Medan - Sanjaya, Surya; Irsan, Muhammad; Pasaribu, Ade Tria Febyanti (Jurnal Riset AKuntansi dan Bisnis, 2025)
This study aims to analyze the contribution of Entertainment Tax and Advertising Tax revenues to the Regional Original Income (PAD) in Medan City in 2021-2023. The problem that occurs in this study is the number of taxpayers for Entertainment Tax and Advertising Tax in Medan City which is increasing but the revenue received does not meet the set target. The research approach used is a descriptive approach and this type of data is qualitative data. The data analysis technique used in this study is a descriptive analysis technique. This study took place at the Medan City Regional Revenue Agency. The results of the contribution analysis show that the revenue of Entertainment Tax and Advertising Tax is classified as very low in contributing to the original regional income of Medan City. The low contribution of Entertainment Tax and Advertising Tax to Regional Original Income is caused by several factors, including the low awareness of taxpayers to carry out their obligations, the existence of taxpayers who do not report, and the financial problems of taxpayers so that they cannot pay their taxes.